2021
DOI: 10.3390/jcm10225332
|View full text |Cite
|
Sign up to set email alerts
|

Transition to Online Education during the COVID-19 Pandemic: Impact of Changes in Alcohol Consumption and Experiencing Hangovers on Academic Functioning

Abstract: In the Netherlands, the 2019 coronavirus (COVID-19) pandemic had a significant impact on daily life, with two extensive lockdowns enforced to combat the spread of the SARS-CoV-2 virus. These measures included the closure of bars and restaurants, and the transition from face-to-face to online education. A survey was conducted among Dutch pharmacy students and PhD-candidates to investigate the impact of COVID-19 lockdown on alcohol consumption, hangovers, and academic functioning. The analysis revealed a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…This article describes the survey and its content. To this extent, the study replicated and extended a recent study on the same topic which had been conducted in the Netherlands [34][35][36].…”
Section: Aim Of the Studysupporting
confidence: 64%
See 1 more Smart Citation
“…This article describes the survey and its content. To this extent, the study replicated and extended a recent study on the same topic which had been conducted in the Netherlands [34][35][36].…”
Section: Aim Of the Studysupporting
confidence: 64%
“…and extended a recent study on the same topic which had been conducted in the Netherlands [34][35][36]. This data descriptor article describes the survey content and the dataset, which has been added as Supplementary Material.…”
Section: Aim Of the Studymentioning
confidence: 96%
“…However, the data are also relevant for other countries around the world, as many other countries also enforced comparable lockdown periods and switched to online education. To a significant extent, the survey content corresponds to a previous survey that we conducted in the Netherlands [40,46,47]. However, the questions, answers, and other specifics (e.g., lockdown periods) were adjusted to the COVID-19 circumstances in Argentina.…”
Section: Discussionmentioning
confidence: 99%
“…Of note is that the observed effects on alcohol consumption are temporary and last only as long as lockdowns are enforced. Research revealed that as soon as lockdown measures were lifted, alcohol consumption patterns quickly returned to pre-COVID-19 levels [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…This group of drinkers deserves attention, and efforts should be made to reduce their alcohol consumption. Moderation of alcohol consumption has been associated with improved health and immune fitness ratings [ 10 ] and better academic functioning [ 57 ]. It should therefore be an important goal of policymakers to support prevention initiatives that aim to reduce heavy alcohol consumption and promote a healthy lifestyle.…”
Section: Discussionmentioning
confidence: 99%